2013
DOI: 10.1111/nhs.12091
|View full text |Cite
|
Sign up to set email alerts
|

Nurse qualifications and perceptions of patient safety and quality of care in South Africa

Abstract: A plethora of research links professional nurses' qualifications to patient outcomes. Also, research has shown that reports by nurses on the quality of care correspond with process or outcome measures of quality in a hospital. New to the debate is whether professional nurses' qualifications impact on their perceptions of patient safety and quality of care. This research aims to investigate professional nurses' perceptions of patient safety and quality of care in South Africa, and the relationship between these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Nurses apply their knowledge, skills and experience to care for the various and changing needs of patients 13 . The quality of care by nurse correspond with outcome measures of quality in a hospital 14 .The present study also illustrates that nurses have a good knowledge and practice regarding safe patient care are and their attitude is positive towards safe patient are. This findings contradict the findings of a study 9 that indicated a quite a low level of safety knowledge among health care professionals.…”
Section: Discussionsupporting
confidence: 64%
“…Nurses apply their knowledge, skills and experience to care for the various and changing needs of patients 13 . The quality of care by nurse correspond with outcome measures of quality in a hospital 14 .The present study also illustrates that nurses have a good knowledge and practice regarding safe patient care are and their attitude is positive towards safe patient are. This findings contradict the findings of a study 9 that indicated a quite a low level of safety knowledge among health care professionals.…”
Section: Discussionsupporting
confidence: 64%
“…The findings in this study are in line with studies from other countries that reported similar commitments from the government and executive management, and their continued role in the initiation, support, and sustainability of quality improvement in priority areas in healthcare in these countries (Hampe, ; Yeh & Lai, ). The role of good governance is an enabling structure for nurse managers to undertake CQI – the absence of which is equated to a lack of organizational structure, policies, procedures, and adequate resources, education, and training to support CQI (Blignaut et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Evidence links hospital cultures that foster sharing and reporting of errors to better patient safety and quality of care [ 23 ]. This should go hand in hand with addressing issues such as poor communication, lack of visible leadership, poor teamwork, lack of reporting systems, inadequate analysis of adverse events and inadequate staff knowledge about safety [ 4 ].…”
Section: Discussionmentioning
confidence: 99%